2014
DOI: 10.1667/rr13580.1
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Low-Dose 56Fe-Ion Radiation Induces Long-Term Epigenetic Alterations in Mouse Bone Marrow Hematopoietic Progenitor and Stem Cells

Abstract: There is an increasing need to better understand the long-term health effects of high-linear energy transfer (LET) radiation due to exposure during space missions, as well as its increasing use in clinical treatments. Previous studies have indicated that exposure to 56Fe heavy ions increases the incidence of acute myeloid leukemia (AML) in mice but the underlying molecular mechanisms remain elusive. Epigenetic alterations play a role in radiation-induced genomic instability and the initiation and progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 53 publications
4
64
0
Order By: Relevance
“…It was detected in numerous in vitro and in vivo , as well as in epidemiological studies; in target tissue and in peripheral or cord blood; in the tissue of exposed subjects in comparison to the tissue of control subjects and was inversely correlated with the levels of an environmental contaminant detected in the same subject. Loss of DNA methylation within the TEs, and L1 particularly, contributes to global DNA hypomethylation [91,93,160], given their abundance in mammalian genomes. Hypermethylation of TEs is a much less frequently reported effect of exposures, and the biological consequences of accumulation of methyl groups within the TEs still need to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was detected in numerous in vitro and in vivo , as well as in epidemiological studies; in target tissue and in peripheral or cord blood; in the tissue of exposed subjects in comparison to the tissue of control subjects and was inversely correlated with the levels of an environmental contaminant detected in the same subject. Loss of DNA methylation within the TEs, and L1 particularly, contributes to global DNA hypomethylation [91,93,160], given their abundance in mammalian genomes. Hypermethylation of TEs is a much less frequently reported effect of exposures, and the biological consequences of accumulation of methyl groups within the TEs still need to be elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to 56 Fe ion radiation selectively targeted transposable elements in the less differentiated hematopoietic stem and progenitor cells, while the effects in mononuclear cells that are primarily comprised of terminally differentiated cells were miniscule [93]. Interestingly, while global, L1-, and SINE B1-associated dose-dependent hypermethylation was observed in hematopoietic stem and progenitor cells 30 days after exposure (similar to abovementioned findings in the lung by Lima et al [92] at the same time-point), global hypomethylation (37% decrease) was observed 22 weeks after exposure to 0.4 Gy of 56 Fe ( 56 Fe +26 , 600 MeV/nucleon) – a dose associated with increased rates of AML [101].…”
Section: Transposable Elements and Ionizing Radiationmentioning
confidence: 99%
“…Expression of LINE-1, the most abundant mammalian retrotransposon that comprises nearly 20% of their genome, is reported to be regulated by DNA methylation and directed by DNA methyltransferases (Bourc'his and Bestor, 2004; Miousse and Koturbash, 2015). Loss of DNA methyltransferases expression may lead to the loss of global and TEs-associated DNA methylation (Jones, 2012; Miousse et al, 2014b; Koturbash et al, 2011). Interestingly, in this study, similar to our previous investigations in vitro,(Lu et al, 2015a) we identified a non-significant trend towards LINE-1 DNA hypermethylation 24 h after exposure to PEPs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, exposure to low mean absorbed doses of 56 Fe (600 MeV, dose range 0.1 – 0.4 Gy), did not lead to increased production of reactive oxygen species, DNA damage or alterations in cellular senescence and apoptosis in the murine hematopoietic progenitor and stem cells (HPSCs). At the same time, exposure to the leukemogenic dose of 0.4 Gy of 56 Fe has led to altered global and repetitive elements-associated methylation of DNA and DNA methylation machinery that were detectable in HSPCs for at least 5 months after irradiation [14]. Accumulating evidence indicates that alterations in DNA methylation is the general feature of space radiation and that these alterations are primary attributable to repetitive elements.…”
Section: Introductionmentioning
confidence: 99%